1999
DOI: 10.1006/dbio.1999.9253
|View full text |Cite
|
Sign up to set email alerts
|

Defective Vascularization of HIF-1α-Null Embryos Is Not Associated with VEGF Deficiency but with Mesenchymal Cell Death

Abstract: Hypoxia-inducible factor 1 (HIF-1) is a dimeric transcription factor composed of HIF-1alpha and HIF-1beta subunits that plays an essential role in mammalian O2 homeostasis. In Hif1a-/- knockout mice, complete deficiency of HIF-1alpha resulted in cardiac and vascular malformations and embryonic lethality at E10.5. Between E8. 75 and E9.25 striking vascular regression and abnormal remodeling occurred in the cephalic region concomitant with marked mesenchymal cell death. Similar vascular defects were observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
263
2
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(275 citation statements)
references
References 41 publications
5
263
2
1
Order By: Relevance
“…The different spatial expression of HIF-1a and HIF-2a may reflect their different roles in pulmonary development. HIF-1a knockout mice suffer from severe cardiovascular defects and die in utero (Kotch et al 1999;Compernolle et al 2003), whereas HIF-2a knockout mice suffer from postnatal respiratory distress due to insufficient surfactant production (Compernolle et al 2002). A heterozygous deficiency in HIF-2a protects mice from developing pulmonary hypertension (Brusselmans et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The different spatial expression of HIF-1a and HIF-2a may reflect their different roles in pulmonary development. HIF-1a knockout mice suffer from severe cardiovascular defects and die in utero (Kotch et al 1999;Compernolle et al 2003), whereas HIF-2a knockout mice suffer from postnatal respiratory distress due to insufficient surfactant production (Compernolle et al 2002). A heterozygous deficiency in HIF-2a protects mice from developing pulmonary hypertension (Brusselmans et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1␣-deficient mouse embryos arrest in their development by d 9 of gestation (E9.0) and die by E10.5 with severe cardiovascular and neural tube defects and massive cell death, especially in the branchial and cephalic regions (7)(8)(9). Mice that are heterozygous for the knockout allele and thus partially HIF-1␣ deficient develop normally.…”
Section: Developmental Biology and Physiologymentioning
confidence: 99%
“…The binding of HIF1a to the target DNA site, in conjunction with HIF1b, leads to transcriptional activation of the downstream genes including the VEGF gene. The studies on HIF1a-de®cient mice have suggested a key role of HIF1a on the VEGF-mediated angiogenesis in response to hypoxia (Iyer et al, 1998;Kotch et al, 1999). In supporting this notion, both HIF1a and VEGF are overexpressed in a wide variety of human cancers (Folkman, 1997;Zong et al, 1999).…”
Section: Introductionmentioning
confidence: 99%